Classification Analysis of The Presentation of Impairment Expenses in The Statement of Comprehensive Income - Aldaka Barus, Samuel; Farah Mita, Aria (Eduvest - Journal of Universal Studies, 2025)
This study investigates the classification practices of impairment expenses for receivables in the comprehensive income statements of companies in the telecommunications sector in Indonesia. Utilizing a qualitative case study approach, the research analyzes financial reports from 2020 to 2023, focusing on the impacts of PSAK 109, which emphasizes expected credit losses. The findings reveal significant variations in how companies classify impairment charges, influenced by factors such as auditor characteristics, business models, and management interpretations of accounting standards. The analysis indicates that many companies still present impairment expenses inconsistently, affecting the transparency and comparability of financial statements. This lack of uniformity complicates decision-making for investors and stakeholders. The research highlights the necessity for improved financial literacy programs and the consistent application of accounting standards to enhance the quality of financial reporting in the telecommunications sector.